AN INVESTIGATION OF RESEARCH ON EVOLUTION OF ALTRUISM USING INFORMETRIC METHODS AND THE GROWING HIERARCHICAL SELF-ORGANIZING MAP - Yu, Hsiang Yang; Rua, Huan Tsaih (Malaysian Journal of Library and Information Science, 2010)
The purpose of this study was to investigate the characteristics of research related to evolution of altruism from 1971 to 2009 within the science citation index expanded (SCIE) and the social science citation index (SSCI) databases. This study showed how the growth of research related to evolution of altruism is a well known phenomenon, that statistics of the Bradford’s Law identified ten core altruism-related journals, and that the altruism-related data does not fit Lotka’s law. We applied Growing Hierarchical Self-Organizing Map (GHSOM), a text-mining Neural Networks tool, to obtain a hierarchical topic map. The topic map illustrated the delicate intertwining of subject areas and provided a more explicit illustration of the concepts within each subject area. Furthermore, the result of the topic map also reflects that evolutionary psychology based on neuroscience and other related discipline will play an importance role in the future exploring into the in-depth motivation of altruism.